Carbon microparticles as a physical carrier for ETV-ICP-MS - Patočka, Jan; Krejčová, Anna; Černohorský, Tomáš; Šlang, Stanislav (Elsevier, 2019)
In this study, carbon microparticles (CMs) as a physical carrier to enhance the analyte transport efficiency for inductively coupled plasma mass spectrometry connected with electrothermal vaporization (ETV-ICP-MS) are proposed. Carbon microparticles mixed with samples or calibration standard solutions were dosed as a slurry into the graphite furnace. The optimization of working conditions was done for the standard solution 0.5 mu g L-1 of Au and Tl. The pyrolysis and vaporization temperatures were 500 and 2700 degrees C for Au and 400 and 1900 degrees C for Tl. The optimized CMs concentration was 1 g L-1 for Au and 2.5 g L-1 for Tl. For the quantification, external calibration standard solutions were used. The result obtained for Au in the digested CRM GBW 07601 (the informatory value 2.1 +/- 2 mu g kg(-1)) was 2.2 +/- 0.1 mu g kg(-1). The result for Tl in the digested CRM BCR 679 (the certified value 3 +/- 0.3 mu g kg(-1)) was 3.2 +/- 0.2 mu g kg(-1) and in the slurry 2.7 +/- 0.1 mu g kg(-1). The result for Tl in the CRM GBW 10052 (the certified value 57 +/- 11 mu g kg(-1)) was 51 +/- 3 mu g kg(-1). The instrumental limits of detection were 0.016 ng L-1 for Au and 0.026 ng L-1 for Tl. The recoveries and repeatabilities measured on calibration standards were in the range 99-100% and 0.2-2.3% for Au and 100-111% and 2.9-6.7% for Tl.
Uhlíkové mikročástice jako fyzický nosič pro ETV-ICP-MS
Keywords: ETV-ICP-MS; Carbon microparticles; Analyte transport efficiency; Slurry samples; Ultra-trace analysis; ETV-ICP-MS; Uhlíkové mikročástice; Účinnost transportu analytu; Analýza suspenzí; Ultrastopová analýza